The relationship between perceptual learning style preferences and language learning strategies of undergraduate ESL learners / Ho Ai Ping - Ho , Ai Ping (2018)
There are many variables that could affect learners’ language learning. Two important individual differences variables that could affect second language performance are language learning styles and language learning strategies. With that in view, this study aimed to determine the overall perceptual learning styles preferences by using Reid’s Perceptual Learning Style Preferences Questionnaire, PLSPQ (Reid, 1987) and the language learning strategies by using Oxford’s Strategy Inventory for Language Learning version 7, SILL (Oxford, 1990a) among 1708 the first year undergraduates in Universiti Malaysia Sarawak (Unimas). Besides, this study also examined whether there was a relationship between perceptual learning style preferences and language learning strategies. Interviews were also conducted to further investigate factors that could affect their perceptual learning styles preferences and language learning strategies. Findings revealed that these undergraduates highly preferred individual learning style and least preferred kinesthetic learning style. As for language learning strategies, metacognitive strategies were highly employed by these learners whereas affective strategies were least used. In addition, finding also revealed a negative significant linear relationship between most perceptual learning style preferences and language learning strategies. It was found that interviewees’ language proficiency, past learning experiences and personality traits were among crucial factors affecting the learners’ perceptual learning style preferences. On the other hand, language proficiency, gender, language learning environment, parents’ socioeconomic status and motivation were the prominent factors influencing the interviewees’ language learning strategies. The results of this study implied language learning styles and strategies could be discussed based on the psychological and sociocultural perspectives.